Penerapan media belajar Canva untuk meningkatkan minat belajar siswa - Salman Fatahillah; Hastari; Madinah; Yayan Sudrajat (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2023)
In every age, education is the most important thing for life and must receive very serious attention. The education system must be of quality so that human life in all aspects improves. In every era that has passed, various things have been found to improve learning, including in this case the media that is always used in every lesson, this learning media has definitely developed according to the times. It is hoped that with the development of the application it can be used as a medium for both teachers and students to interact in the teaching process.